Trichotomy in Visual and Written Text of the Honor of Kings Advertisement: A Semiotic Case by Peirce - Edelwis Chairunnisa; Dewi Kustanti; R. Myrna Nur Sakinah (Prodi Tadris Bahasa Inggris, 2025)
This study analyzes the use of semiotic signs in advertisements for the popular MOBA game Honor of Kings through Peirce's trichotomy theory. The research focuses on analyzing the visuals and written text in the ads to understand how these elements convey messages. Descriptive qualitative method with data collection through purposive sampling method was applied in this research. From the 38 data that the author found, 11 data were taken in the form of 7 visuals and 4 written texts from two video advertisements entitled “Welcome to Honor of Kings” and “Honor of Kings Launch Date Trailer.” The research findings reveal that the combination of visual and written text creates a cohesive and continuous narrative that increases audience engagement and interest. This study contributes to the field of semiotics and marketing by showing how semiotic elements in advertising can shape meaningful and effective communication strategies. The findings offer insights for marketers and academics on improving message delivery in digital media through semiotic signs.